Guided Recreational Training as a Catalyst for Improving Agility, Flexibility, and Motor Coordination in 16-Year-Old Youth Football Players - Laith Rasim Abbas; Ali Abdulameer Jabbar; Sanaa Abdul Al-Ameer Al-Kikani; Ameer Ayyed Abdalaimah; Mohammed Hasan Shaalan Obed; Hussein Hamzah Najm; Fadhil Abd Faidhi; Waheb Razzaq Jebur (CV. FOUNDAE, 2026)
Background: Adolescence at 16 years is a critical stage for developing agility, flexibility, and coordination in football players. Globally, many adolescents fail to meet recommended physical activity levels, and organized sports participation often declines due to burnout and low engagement. Structured recreational training can enhance motor skill development while fostering motivation, engagement, and psychosocial growthAim: This study aims to implement a guided recreational training program specifically designed to enhance agility, flexibility, and coordination in 16-year-old youth football players in Iraq, addressing the research gap related to the limited availability of multi-component programs in resource-constrained settingsMethods: Forty-eight male football players were randomly assigned to an experimental group (n = 20) and a control group (n = 20), with a pilot group of eight participants used to refine testing instruments. Over 12 weeks, the experimental group completed 24 recreation-based sessions (2 sessions/week, 1 hour each), while controls followed regular training. Agility, flexibility, and coordination were assessed pre- and post-intervention, and regression analysis examined program effects.Result: The experimental group showed significant improvements over controls in all variables: agility (t = -39.920, p < 0.001), flexibility (t = 24.724, p < 0.001), and coordination (t = -26.726, p < 0.001). Regression analysis indicated no significant effect of pre-test scores on agility and coordination, while flexibility had a modest predictive effect (B = 0.217, p = 0.040).Conclusion: Guided recreation-based training effectively sustained motivation and engagement, enhancing acquisition and application of motor skills. Integrating structured recreational components into adolescent football programs can overcome limitations of conventional methods, promoting skill diversity, stronger motivation, and enjoyable learning experiences.